Student centred learning - the paradigm of modern higher education - Ćirić, Marina D.; Petrović, Jelena S.; Jovanović, Dragana R. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2020)
Student centered learning implies the pedagogical approach based on constructivism and theories related to it, and it is characterized by the methods used to make a student actively contribute the learning process. It is recognized in the mindset and culture of the faculty, and focused on the needs and opinions of students. This paper presents the main elements of this approach in the context of higher education system. It starts with the perspective that placing the student at the center, the “heart” of the educational process, is a response to numerous social challenges and the reform process. The first part of the paper highlights a dichotomy resulting from the need to reconceptualize the traditional educational system in order to respond the needs of the knowledge society. It further points out the particularities and the differences between the teaching paradigm and the learning paradigm and elaborates the (im)possibilty of combining them. The second part of the paper is dedicated to the analysis of the possibilities for implementing student-centered approach in higher education institutions and making it an integrative part of their climate and learning culture.
Keywords: higher education; paradigm; reform; teaching methods; students